Cuzco Main Square: Founding Myths and Stories of Destruction - Lucas Alonso, Patricia (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2012)
Cuzco Main Square is one of the public spaces in Peru with more mythic significance. Lima was founded in colonial times, but Cuzco was the capital of the Inca Empire and was related to several founding myths. Spanish conquest and colonization created a radical cultural mix. In those times, the square becomes the scene of events of great violence as the execution of Tupac Amaru II. Myths of birth were then joined to stories of destruction and death. Local population created then new resistance strategies. This paper aims to review briefly some stories related to this space. Some of them were registered in ancient chronicles, for instance in Comentarios reales, and others are now part of a rich folk culture. Stories of birth and death are connected to this square. Maybe, it is possible to think in it as an urban myth.
Keywords: Peru; Cuzco; Main Square; Inca Garcilaso; Tupac Amaru.